Improved irradiation resistance of Cr-Fe alloy for Cr-coated Zircaloy application in accident tolerant fuel. (May 2023) - Cui, L.J.; Du, Y.F.; Yang, H.L.; Jovellana, J.A.K.; Shi, Q.Q.; Kano, S.; Abe, H.
Abstract: Cr coating onto Zircaloy for the application of accident tolerance fuel claddings became a popular topic in the nuclear material field since the Fukushima-Daiichi accident in 2011. However, in the Cr coating layer the solute element effect on the potential performance improvement is still unknown, especially under irradiation. The irradiation effect in Cr-7Fe was studied after irradiation by 2.8 MeV Fe 2+ to 20 dpa at 550 °C. The nano-indentation results show that doping of Fe not only can strengthen the material but also can significantly reduce the irradiation-induced hardness compared with pure Cr. The microstructure analyses show that solute element Fe can retain the diffusion of defects and reduce void swelling. In addition, the APT results indicate that no detrimental Fe-rich cluster formed in irradiated Cr-7Fe. From the aspects of irradiation-induced hardening, void-swelling, and clustering, a great improvement in irradiation resistance was achieved in Cr-7Fe alloy compared with pure Cr. Graphical abstract: Image, graphical abstract